Peluang dan Tantangan Bantuan Hukum di Daerah Pedesaan - Elisa; Rahmah, Siti; Putra, Bambang Sasmita Adi (Indra Institute Research & Publication, 2024)
Providing legal aid in rural areas is a crucial effort to ensure access to justice for all levels of society, especially for those who are less fortunate. Key opportunities for providing legal aid in rural areas include increasing legal awareness, strengthening community participation in legal processes, and increasing local capacity through legal education. Legal assistance in rural areas can also strengthen social cohesion and speed up the resolution of local and customary-based disputes. However, the challenges faced in providing legal aid in rural areas are not small. These challenges include limited human resources who are competent in the legal field, limited infrastructure and accessibility, as well as low levels of legal literacy among rural residents. In addition, difficulties in integrating the formal legal system with local customary law also add to the complexity of providing legal assistance. A deep understanding of the local context and approaches that adapt to the specific needs of rural communities are needed to address these challenges. This research discusses the opportunities and challenges that exist in providing legal aid in rural areas with a focus on providing inclusive and sustainable services. The strategic recommendations offered include improving legal education, strengthening cooperation networks between government, non-government organizations and local communities, as well as developing a more equitable legal infrastructure. A participatory and community-based approach is expected to increase the effectiveness of legal aid and ensure that justice can be accessed by all citizens, regardless of their geographical location.